2015
DOI: 10.1128/jvi.03304-14
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hemagglutinin Receptor-Binding Specificity Accompany the Emergence of Highly Pathogenic Avian Influenza Viruses

Abstract: Highly pathogenic avian influenza viruses (HPAIVs) of hemagglutinin H5 and H7 subtypes emerge after introduction of lowpathogenic avian influenza viruses (LPAIVs) from wild birds into poultry flocks, followed by subsequent circulation and evolution. The acquisition of multiple basic amino acids at the endoproteolytical cleavage site of the hemagglutinin (HA) is a molecular indicator for high pathogenicity, at least for infections of gallinaceous poultry. Apart from the well-studied significance of the multibas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
1
13
0
3
Order By: Relevance
“…Previous studies suggested that the functional balance between HA (receptor binding) and NA (receptor destroying) contributes to pathogenicity and host range of influenza A viruses [28]. Nevertheless, the mechanism by which NA contributes to virus–glycan interaction has not been extensively studied because analyses on interaction of NA with modified α2,3 sialosides are still limited [29]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the functional balance between HA (receptor binding) and NA (receptor destroying) contributes to pathogenicity and host range of influenza A viruses [28]. Nevertheless, the mechanism by which NA contributes to virus–glycan interaction has not been extensively studied because analyses on interaction of NA with modified α2,3 sialosides are still limited [29]. …”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to point out that it is very important to monitor the receptor-binding characteristics of the circulating and emerging influenza A and B viruses because the repertoire of HA receptors defines tissue tropism and, consequently, virulence of the virus [5,6]. Thus, the patients infected with the influenza B virus strains that bind not only to the SAa2-6Gal-chains but also SAa2-3Gal ones (avian type) are prone to developing pneumonia and more often have the symptoms of gastrointestinal tract damage [11].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the avian influenza A viruses have an affinity predominantly for hydrocarbons with the a2-3 glycoside bond between SA and the neighboring galactose (GA) residue while the human influenza A viruses interact mostly with the SAa2-6Gal chains [1][2][3][4]. The receptor-binding specificity of the influenza A viruses had been studied in detail and it is considered to be one of the factors that influence virus pathogenicity [5,6]. As regards the receptor-binding specificity of influenza B viruses, there is rather limited data available [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Аминокислотный остаток в позиции 242 (замена Ser на Arg) также может влиять на репер-туар рецепторов вируса гриппа B/Флорида/04/2006. Необходимо подчеркнуть, что очень важно осу-ществлять мониторинг рецепторсвязывающих ха-рактеристик циркулирующих и вновь появляющих-ся штаммов вирусов гриппа как А, так и В, поскольку структура рецепторов вируса определяет его ткане-вой тропизм, а значит, и вирулентный фенотип [5,6]. Так, уже показано, что пациенты, инфицированные штаммами вируса гриппа В, которые связываются не только с SAα2-6Gal-звеньями, но и с сиалозидами «птичьего» типа (SAα2-3Gal), более склонны к раз-витию бронхопневмонии и чаще имели симптомы поражения желудочно-кишечного тракта [11].…”
Section: зак лючениеunclassified
“…Известно, что вирусы гриппа А птиц преимуще-ственно имеют сродство к углеводам с α2-3 гликозид-ной связью между SA и соседним остатком галактозы (Gal), тогда как вирусы гриппа А человека взаимодей-ствуют преимущественно с SAα2-6Gal-цепями [1][2][3][4]. Рецепторсвязывающая специфичность вирусов грип-па A детально изучена и считается одним из факто-ров патогенности [5,6]. Что касается вирусов гриппа В, то данных по рецепторсвязывающей специфично-сти НА этих вирусов крайне мало [7][8][9].…”
Section: Introductionunclassified